Funkcionalizmus a vezetésben : a magyarországi kutatás eredményei - Berde, Csaba (Közép-Európai Közlemények, 2010)
For the research of managerial questions, We worked out a program called „The functional study of corporate management”, which starts out from the examination of managerial tasks.Its approach is functional, and as it is based on corporate, practical experiences, it is empirical, too.The applied experimental method of mine is built up of moduls, these contain separately researchable moduls, certain moduls form a part of a larger researchal subject. The individual subjects generate a more comprehensive researchal field. These subjects, partial subjects are organized into a privately prepared structure proper to systematize managerial tasks, these can be widened and tightened horizontally, vertically, concentrated and these can be broken into smaller parts. To examine the diverse subjects of management, it provides a uniform methodological frame, through this enables the comprehensive and harmonized research of different managerial tasks and activities. Since this researchal method aims to examine managerial tasks, it is suitable for opening and analyzing those special managerial problems, which are the charasteristics of the corporate processes.